The Effect of Noisy Galvanic Vestibular Stimulation on Learning of Functional Mobility and Manual Control Nulling Sensorimotor Tasks - Putman, Esther J.; Galvan-Garza, Raquel C.; Clark, Torin K. (Frontiers in Human Neuroscience, 2021)
Galvanic vestibular stimulation (GVS) is a non-invasive method of electrically stimulating the vestibular system in order to enhance vestibular motion perception and related performance. We investigated whether the application of GVS can alter the learning of new functional mobility and manual control tasks and whether learning can be retained following GVS application. Normal, healthy subjects performed repeated trials, capturing the learning of either a) a functional mobility task, navigating an obstacle course on a compliant surface with degraded visual cues, or b) a manual control task, using a joystick to null self-roll tilt against a pseudo-random disturbance while seated in the dark. In the ‘learning’ phase of trials, bilateral, bipolar GVS was applied continuously. However, in a between-subjects design, the GVS waveform differed between groups: 1) white noise GVS (nGVS) at 0.3 mA 2) high-level random GVS at 0.7 mA (selected from pilot testing as destabilizing, but not painful), or 3) with the absence of stimulation (i.e., sham). Following the ‘learning’ trials, all subjects were blindly transitioned to sham GVS, upon which they immediately completed another series of trials to assess any aftereffects. In the functional mobility task, we found nGVS significantly improved task learning (p=0.03, mean learning metric 171% more than the sham group). Further, improvements in learning the functional mobility task with nGVS were retained, even once the GVS application was stopped. The benefits in learning with nGVS were not observed in the manual control task. High level GVS tended to inhibit learning in both tasks, but not significantly so. Even once the high-level stimulation was stopped, the impaired performance remained. Improvements in learning with nGVS may be due to increased information throughput resulting from stochastic resonance. The benefit of nGVS for functional mobility, but not manual control nulling, may be due to the multisensory (e.g., visual, proprioceptive), strategic, motor coordination, or spatial awareness aspects of the former task. Learning improvements with nGVS have the potential to benefit individuals who perform functional mobility tasks, such as astronauts, firefighters, high performance athletes, and soldiers.